Angiogenic and anti-angiogenic factors during the post-hatching growth of the quail (Coturnix coturnix japonica) spleen - Bayram, Bayram; Liman, Narin; Alan, Emel; Sagsoz, Hakan (Wiley, 2024)
Vascular endothelial growth factor (VEGF) family members are responsible for endothelial cells' growth, proliferation, migration, angiogenesis, vascular permeability, and differentiation and proliferation of non-endothelial cell types. VEGF and its receptors are found in mammalian lymphoid organs. The present study was conceived to determine (a) the presence and localization of angiogenic VEGF and its receptors (Fms-like tyrosine kinase 1 [Flt1/fms], fetal liver kinase 1 [Flk1]/kinase insert domain receptor [KDR], Fms-like tyrosine kinase 4 [Flt4]) and vascular endothelial growth inhibitor (VEGI) in the quail spleen; and (b) whether their expressions in the spleen components change during the post-hatching growth of the organ, using immunohistochemistry. Immunohistochemical stainings showed that VEGI, VEGF, and VEGF receptors were expressed in many components, including the vascular endothelial and smooth muscle cells, ellipsoid-associated cells (EACs), and immune cells, of quail spleen and that VEGF and its receptors' immunostaining intensity scores (ISs) varied depending on the post-hatching growth period, while VEGI-IS did not change. In addition, ISs of VEGI, VEGF, Flt1/fms, and Flt4 in EACs were weak to moderate, while flk1/KDR-IS in EACs adjacent to the capsule of Schweigger-Seidel sheaths (ellipsoids) was higher than other proteins, supports a more important and specific role of Flk1/KDR in the EAC function. These specific expressions of VEGI, VEGF, flt1/fms, flk1/KDR, and flt4 proteins in splenic cell types suggest their particular roles, in the functional development of splenic components and thus, are critical to post-hatching maturation of quail spleen. These findings indicate that the expression levels of VEGF, Flt1/fms, and Flt4, except Flk1/KDR, are low in the quail spleen, and only a few components of the spleen express VEGF, Flt1/fms, and Flt4 under normal conditions.
Keywords: development; immunohistochemistry; spleen; VEGI